Roll of thunder, hear my cry - Taylor, Mildred D. (New York : Bantam Books, 1978)
A black family living in the South during the 1930's are faced with prejudice and discrimination which their children don't understand.
920
Newbery medel award winner.
Keywords: African Americans -- Fiction; Southern States -- Race relations -- Fiction; Southern States -- Race relations -- Fiction